Back-up procedures following complicated gastric pull-up procedure for esophageal reconstruction: Salvage with intestinal flaps - SAÇAK, BÜLENT (WILEY-BLACKWELL, 2016)
BackgroundGastric pull-up (GPU) is the most common procedure for restoring the continuity of the alimentary tract. Yet, complications because of anastomotic problems are reported to be as high as 25% after this procedure. Managing the neck with anastomotic leakage or stricture following failed GPU and/or radiotherapy is formidable. We report our method, basic algorithm and results with the complicated GPU procedure management with intestinal transfers . Patients and methodsNineteen cases referred to our department with complicated esophageal reconstruction following GPU procedure were included in this report. Of the19 patients, 18 had undergone GPU procedure for reconstruction after cancer resection (mean age 55 years) and one for idiopathic esophagitis (mean age 45years). Fifteen patients presented with severe stricture formation and 4 patients with leakage from the anastomotic site. Average time between the GPU and salvage procedures was 7.3 months for patients with stricture formation and 15.5 days for patients with leakage. Pedicled colon interposition (n=8) was used when the upper end of the gastric tube was located below the sternoclavicular junction. A free jejunal flap (n=11) was utilized when defects were located at the neck (above the sternoclavicular junction). ResultsIn all patients salvage procedures with intestinal flap transfer were successful with complete flap survival. Post-operative period was uneventful except of two patients with pedicled colon interposition who presented minor leakage post-operatively (10.5%). This was treated with conservative means, leading to spontaneous healing. The average follow-up for the patients with tumor resection was 11.8 months (range: 6 to 30) after the salvage procedure. All patients resumed smooth oral intake eventually. There were 16 patients who could feed with solid diet, whereas three patients were able to tolerate only soft diet. ConclusionIntestinal tissues can be safely and successfully transferred as salvage procedures, with meticulous technique, careful patient selection and individual flap design. While gastric pull-up remains a good procedure for esophageal reconstruction, the methods described in this report are useful as back-up armaments in complicated cases. (c) 2015 Wiley Periodicals, Inc. Microsurgery 36:567-572, 2016.
Keywords: MAJOR MUSCLE FLAP; PHARYNGOESOPHAGEAL RECONSTRUCTION; SKIN FLAPS; INTERPOSITION; CARCINOMA; RESECTION; OUTCOMES; JEJUNUM; VEIN